Road maintenance management system in Kendari City, Southeast Sulawesi, Indonesia - Buburanda, Mahmud; Rianse, Usman; Alwi, La Ode; Ade Putra, Adris (Technium Social Sciences Journal, 2023)
This study aims to determine road conditions and determine the sustainability of road maintenance management in Kendari City in terms of social, economic and environmental aspects. This research was conducted through observation and data collection from the community regarding the management of highway maintenance by using the attributes of social, economic and environmental parameters. Data analysis used in determining the sustainable highway maintenance management index uses the RAT-HMM (Rapid Assessment Techniques for Highway Maintenance Management) Program. The results showed that the road conditions in Kendari City were in the Light to Moderate Damage Category with maintenance road status, namely Periodic Maintenance to Rehabilitation. In addition, this study also shows that the results of the assessment of all aspects of the social, economic and environmental dimensions are in the Sufficiently Sustainable category (> 64 – 72%) in the construction and maintenance of roads in Kendari City. Therefore, road maintenance management governance policies are still needed in Kendari City.